Intellectual Capital in hospitals- Opportunities and limitations of external intellectual capital reporting - Weichselbaumer, Barbara (2013)
Hospitals, like other knowledge-intensive organizations are today more dependent than ever before on intellectual capital (IC). lC consists of non-physical sources of knowledge used for value creation for key stakeholders. It comprises of human, structural and relational capital and becomes more often the key point for sustainable competitive advantage. The respective value is generally not reflected in the balance sheet. Indeed there are possibilities to disclose information on IC in supplementary or annual reports in order to reduce the lack of information on value drivers. The German hospital market is in a significant transition and trends of privatization, consolidation and a rising need for external capital become apparent. This increases the necessity for determination of a hospitals' value and key value drivers. The aim of the present thesis is to answer the questions of how IC in hospitals is measured and the how the information is disclosed to answer consequently the question if the analyzed tools can show the added value gained by IC. Finally, the analysis should find an answer on whether the reports can influence the valuation of hospitals and create a positive effect. The study is based on data gathered by five external available reports of national and international hospitals comprising information IC. The analysis includes both an examination of extent and quality of IC disclosure through the usage of content analysis and a disclosure index derived from previous studies and aligned to the special field of interest. Additionally, the reports were analyzed whether or not certain requirements set by financial analysts for valuation are met. The results show that IC disclosure in hospitals can be provided with or without making use of frameworks for IC reporting, or by including the information in annual reports.